The Effectiveness of Utilizing Durian Peel Waste (Durio Zibethinus) and Rambutan Peel Waste (Nephelium Lappaceum) As Adsorbents for Water Exposed to Used Oil Waste - Halim, chandra; Helmayanti, Novia; Sastri Candra Maharaja, Nia Sastri Candra Maharaja (ASIAN PUBLISHER, 2023)
Water is a necessity for all living things, including humans, animals and plants. On the other hand, the human environment is exacerbated by the presence of seasonal fruit waste such as durian fruit (Durio Zibethinus) and rambutan fruit (Nephelium Lappaceum), which have a large amount of production. Used oil waste is waste that is classified as B3 (Hazardous and Toxic Material) waste originating from industrial factory residues, spilled vehicle oil that threatens the life of terrestrial and marine biota so that it can cause poisoning. The research methods used are literature study and experimental methods. The literature study method is used to examine references to related information about durian skin waste, rambutan, used oil waste which can be used as secondary data. The experimental method is used to obtain research results by conducting structured activities to obtain conclusions. This study used two variations, namely variations in contact time of 0.5 hours to 3.5 hours with a difference of 0.5 hours for each variation with the composition of durian peel and rambutan peel waste of 3 g each for each variation. The next variation is the variation in composition, namely the variation of durian peel waste and rambutan peel waste of 1:1, 1:2, 2:1 with the same contact time of 2 hours. the combination of durian peel waste and rambutan peel waste can be used as an adsorbent for water pollution exposed to waste oil. The resulting contact time variation is 3.5 hours with an effective adsorption coefficient of (538.88 ± 9.62)% with a mass absorbed of (32.33 ± 0.57) g. Meanwhile, the optimal composition variation is the variation of durian and rambutan peel waste composition of 1:2 with an adsorption percentage of (591.67 ± 14.43)% with an absorbed mass of (23.66 ± 0.57) g.